Web-Based E-Commerce Using Up Selling and Safety Stock Methods - Amanda, Widia Putri; Samsudin (Information Technology and Science (ITScience), 2025)
This research examines the application of the e-commerce platform at the An-Nur Muslim Shop which sells Hajj and Umrah equipment. In the rapidly developing digital era, e-commerce has become essential for companies to expand market share and increase operational efficiency. E-commerce is changing the traditional way of commerce, allowing customers to shop easily and safely. The principle of fair and legal transactions in Islam is an important basis for the development of e-commerce, as emphasized in QS An-Nisa: 29. The Up Selling method is applied to increase sales by offering similar products that have a higher value, which is expected to encourage customers to buy more products. Up Selling works by sorting products from lowest to highest price and offering discounts and special promos on products that meet the criteria. In addition, the Safety Stock concept is used to manage inventory more efficiently. Safety Stock helps anticipate demand uncertainty and delays in receiving raw materials, maintaining optimal stock levels. With this approach, An-Nur Moeslim Shop’s can keep stock levels low to reduce inventory management costs and match new orders only when stock is low. The proposed e-commerce system will allow users to search for products, review descriptions and prices, and make purchases easily through a user-friendly web interface. It is hoped that this e-commerce platform will strengthen An-Nur Moeslim Shop’s position in the market, provide significant added value, and improve the overall customer shopping experience.